THE EDUCATIONAL AND UPBRINGING IMPORTANCE OF THE MOTHER TONGUE FOR PRIMARY SCHOOL STUDENTS - Kurbanova Gulshan Berdimurodovna (Sciental Journals Publishing, 2025)
This article analyzes the educational and educational significance of the native language subject for primary school students from a scientific and pedagogical point of view. It highlights the role of native language lessons in developing oral and written speech, expanding the scope of thinking, and forming national values and moral qualities in students. The article also shows ways to increase the effectiveness of the native language subject through modern educational technologies, interactive methods, and communicative approaches. The results of the study serve to determine the role of the native language subject in primary education in the comprehensive development of the student's personality.
Keywords: Primary education, mother tongue science, educational significance, educational significance, speech development, communicative approach, interactive methods, national values, formation of the student's personality.